G555(P) What Matters to Me? – Flipping Healthcare in Paediatrics. (27th April 2016) - Henderson, J; Stewart, P; Keaney, A
Abstract : Aims: To meet the emotional and psychological needs of the child and the family admitted to hospital, as well as their medical needs. Method: From October 2014, each child admitted to the Paediatric Intensive Care Unit (PICU) had a specially designed laminated "What Matters to Me (WM2M)" card displayed at the bedside, completed by both the parents and (where possible) the child. This was a simple way to formally transfer more personal information, including likes and dislikes, from one member of staff to another. On the reverse, there was a feedback questionnaire to grade the use of the cards from "very good" to "very poor", as well as an area for any other comments. Results: Across the initial 18 weeks of use, 85.7% of patients received a WM2M card. Feedback was taken from parents, patients and nursing staff. 54.8% of the WM2M cards had feedback completed. A total of 39.5% found the cards "very good" (26.3% of these were parents/patients and 13.2% nursing staff). 60.5% found the cards "good" (28.9% of these were parents/patients and 31.6% nursing staff). No one selected "poor" or "very poor". Other wards began to take on the project after hearing staff and families commenting on the cards. This also included patients going to theatre. Furthermore, The Institute for Healthcare Improvement (IHI) presented a short presentation on the project after they heard about the cards, during a keynote speech at their 26 th Annual National Forum in Orlando Florida. Conclusions: Instead of asking our patients "What's the matter with you?" we also ask them "What matters to you?" This is what the IHI call "flipping healthcare". Children are to be recognised as NHS consumers in their own rights. There should be less barriers to accessing their views and experiences 1 of which we hope our WM2M cards have help to do.